Therapeutic Efficacy of Different Ear Cleanser in Management of Canine Otitis - Parmar, Jignasha M; Raval, SK; Parwari, Mayank; Rao, Neha; Patel, DM (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The objective of this study was to compare the therapeutic efficacy of three different ear cleansers in 30 dogs of various breeds suffering  from otitis. Based on history and clinical signs, ear exudates were collected by aseptic cotton swab for isolation and identification of  organisms. The cerumen deposition in-ear canal was cleared using one of the ear preparations, viz., ear cleanser-I (0.2 % salicylic acid  and 0.3 % phenoxyethanol) ear cleanser - II (chlorhexidine, propylene glycol and tris–EDTA) or ear cleanser-III (2% para-dichlorobenzene,  benzocaine 2.7%, chlorbutol 5% and turpentine oil 15 %). Systemic/local antibiotics were used as per sensitivity testing. The treatment  protocol found effective in the management of ear infections included cleaning the ear debris using ceruminolytic preparations/ear  wax dissolvent, viz, ear drop. Ear cleanser-III showed excellent results (100%) in ceruminous as well as bacterial otitis with subsequent  instillation of ear preparations containing antibacterial drug(s) and antifungal agents compared to cleanser-II (90%) and cleanser-I (70%).
Keywords: Canine otitis; Dogs; Ear cleanser; Therapeutic Management